Burden of hypothyroidism amongst type 2 diabetics and hypertensives in Lucknow: A cross sectional study - Kashyap, Saurabh; Khan, Mohammad Suhail; Khan, Anas Ahmad; Idris, M Z; Ahmad, Ausaf; Verma, Sheetal (Indian Journal of Community Health, 2020)
Background: The prevalence of hypothyroidism is reported in 4%–5% of population in the developed world, while in Indian population it is reported in around one in ten adults. Aims & Objectives: This study was conducted to determine the prevalence of hypothyroidism in Indian patients with T2DM and hypertension. Material and methods: In this cross-sectional observational study, amongst adults who were aged 18 years and above and diagnosed T2DM, HTN, and T2DM + HTN who resided in the field practice areas of the Urban Health Training Centre of the Department of Community Medicine, Integral institute of medical sciences and research, Lucknow, India. The results were summarized by descriptive statistics. Results: Out of 300 persons questioned, 159 (53.0%) were females and 141 (47.0%) were males. It was found that the mean age of the overall population was 53.1±11.3 years, mean and standard deviation of thyroid function and glycemic indicators test, observed that the levels of fT3, fT4, TSH, and glycemic indicators like FPG, PPG and HbA1c were identical. Conclusion: Subclinical hypothyroid subjects should be regularly screened for HTN. Elderly patients had higher proportion of thyroid dysfunction.